Crowdsourcing priorities: a new participatory ex-ante framework for crop improvement - Occelli, Martina; Rubin, Deborah; Tufan, Hale Ann (Frontiers Media, 2023)
Demand-led approaches to crop breeding involve ranking priorities across different disciplines and stakeholder categories, but the implications of decisions made during varietal development are frequently understood only years later. Breeding teams must work a priori to rank crop improvement priorities and product concepts considering the context of the current, and ideally future, environmental, production and market conditions that a variety will be entering upon release. We propose PEEP (Participatory Ex-antE framework for Plant breeding), a new ex-ante framework, as a methodological tool for priority setting in plant breeding. PEEP leverages two elements: the usage of a heterodox methodological approach and the strong emphasis on the participation of knowledge-rich stakeholders. PEEP ranks crop improvement impacts based on a heterogenous set of environmental, social, and economic benefits and it employs a recursive and tailored multi-stakeholder approach to relate crop improvement impacts and product concepts. PEEP builds on the need to engage technical as well as practical knowledge and utilizes a tailored engagement strategy for each knowledge-rich stakeholder involved. The outcome is an assessment that ranks crop improvement impacts and breeding product concepts according to designed set of criteria. PEEP is scalable, gender inclusive, and crop agnostic. The results of PEEP are ex-ante recommendations for breeding teams in National Agriculture Research centers (NARs) and CGIAR centers alike. This methods manuscript describes the theoretical foundations of PEEP and its four phases of implementation.